Can a Healthy Lifestyle Compress the Disabled Period in Older Adults?. Issue 10 (7th September 2016) - Jacob, Mini E.; Yee, Laura M.; Diehr, Paula H.; Arnold, Alice M.; Thielke, Stephen M.; Chaves, Paulo H. M.; Gobbo, Liana Del; Hirsch, Calvin; Siscovick, David; Newman, Anne B.
Abstract : Objectives: To determine whether lifestyle factors, measured late in life, could compress the disabled period toward the end of life. Design: Community‐based cohort study of older adults followed from 1989 to 2015. Setting: Four U.S. communities. Participants: Community‐living men and women aged 65 and older (N = 5, 248, mean age 72.7 ± 5.5, 57% female, 15.2% minority) who were not wheelchair dependent and were able to give informed consent at baseline. Measurements: Multiple lifestyle factors, including smoking, alcohol consumption, physical activity, diet, body mass index (BMI), social networks, and social support, were measured at baseline. Activities of daily living (ADLs) were assessed at baseline and throughout follow‐up. Years of life (YoL) was defined as years until death. Years of able life (YAL) was defined as years without any ADL difficulty. YAL/YoL%, the proportion of life lived able, was used to indicate the relative compression or expansion of the disabled period. Results: The average duration of disabled years was 4.5 (out of 15.4 mean YoL) for women and 2.9 (out of 12.4 mean YoL) for men. In a multivariable model, obesity was associated with 7.3 percentage points (95% confidence interval (CI) = 5.4–9.2) lower YAL/YoL% than normal weight. Scores in the lowest quintile of the Alternate Healthy Eating Index were associated with a 3.7% (95% CI = 1.6–5.9) lower YAL/YoL% than scores in the highest quintile. Every 25 blocks walked in a week was associated with 0.5 percentage points (95% CI = 0.3–0.8) higher YAL/YoL%. Conclusion: The effects of healthy lifestyle factors on the proportion of future life lived free of disability indicate that the disabled period can be compressed, given the right combination of these factors.